Palynotaxonomy of species and genera of the Cyanocladus and Trichocladus clades (Lamiaceae: Hyptidinae) - de Carvalho, Renata Jacomo Paixão; Harley, Raymond Mervey; Pastore, José Floriano Barêas; Mendonça, Cláudia Barbieri Ferreira; Gonçalves-Esteves, Vania (Review of palaeobotany and palynology, 2026)
This study analyzed the pollen morphology of 22 taxa of the Cyanocladus and Trichocladus clades. The aim was to describe and characterize pollen grains and assess whether pollen morphology corroborates the recent taxonomy of the group. Only genera occurring in Brazil were studied, including Cyanocephalus (Pohl ex Benth.) Harley & J.F.B.Pastore (7 spp.), the endemic genus Eplingiella Harley & J.F.B.Pastore (3 spp.), Marsypianthes Mart. ex Benth. (4 spp.), Martianthus Harley & J.F.B.Pastore (3 spp.), and Medusantha Harley & J.F.B.Pastore (5 spp.). Acetolyzed pollen grains were measured, described, and photomicrographed. Non-acetolyzed pollen grains were examined by scanning electron microscopy. All taxa analyzed have pollen grains shed in monads, medium to large in size, isopolar, (4)-6-(8–10)colpate, ranging from suboblate to prolate, with a small to very small polar area. The colpi are long to very long, broad, with ornamented membranes and an acute apex, and lack distinct margins. An operculum was observed in all species of Cyanocephalus. The sexine is bireticulated in all other species and genera. The results showed that the pollen morphology of the studied genera was informative in classifying taxa and distinguishing genera, demonstrating some notable parallels with current taxonomic opinion. In principal component analysis and hierarchical cluster analysis, morphometric characteristics approximated and grouped, respectively, species of the genera Eplingiella and Martianthus. These genera exhibited great variation in pollen shape. •Pollen from 22 taxa of the Cyanocladus and Trichocladus clades has been described.•Pollen morphology was informative in classifying taxa and distinguishing genera.•This study describes pollen attributes important for the taxonomy of Lamiaceae.•Pollen morphology supports or disproves the classification of Hyptidinae.